Your body : the missing manual : the book you should have been born with - MacDonald, Matthew (Missing manual., 2009)
What, exactly, do you know about your body? Do you know how yourimmune system works? Or what your pancreas does? Or the myriad --and often simple -- ways you can improve the way your bodyfunctions? This full-color, visually rich guide answers these questions andmore. Matthew MacDonald, noted author of Your Brain: TheMissing Manual, takes you on a fascinating tour of your bodyfrom the outside in, beginning with your skin and progressing toyour vital organs. You'll look at the quirks, curiosities, andshortcomings we've all learned to live with, and pick up justenough biology to understand how your body works. You'll learn: That you shed skin more frequently than snakes do Why the number of fat cells you have rarely changes, no matterhow much you diet or exercise -- they simply get bigger orsmaller How you can measure and control fat That your hair is made from the same stuff as horses'hooves That you use only a small amount of the oxygen you inhale Why blood pressure is a more important health measure thanheart rate -- with four ways to lower dangerously high bloodpressure Why our bodies crave foods that make us fat How to use heart rate to shape an optimal workout session --one that's neither too easy nor too strenuous Why a tongue with just half a dozen taste buds can identifythousands of flavors Why bacteria in your gut outnumbers cells in your body -- andwhat function they serve Why we age, and why we can't turn back the clock What happens to your body in the minutes after you die Rather than dumbed-down self-help or dense medical text, Your Body: The Missing Manual is entertaining and packedwith information you can use. It's a book that may well change yourlife. Reader comments for Your Brain: The Missing Manual, also by author Matthew MacDonald: "Popular books on the brain are often minefields of attractive butinaccurate information. This one manages to avoid most of the hypeand easy faulty generalizations while providing easy to read anddigest information about the brain. It has useful tricks withoutthe breathless hype of many popular books."--Elizabeth Zwicky, The Usenix Magazine " ... a unique guide that should be sought after by any who want tomaximize what they can accomplish with their mental abilities andresources." -- James A. Cox, The Midwest Book Review - WisconsinBookwatch "If you can't figure out how to use your brain after reading thisguide, you may want to return your brain for another." -- TheSacramento Book Review, Volume 1 ...